Folha de São Paulo, pena de morte e justiça: o que trazem os editoriais, jornalistas, convidados e leitores? - Leal, Tatiana Cavalcanti de Albuquerque (2017)
The death penalty is currently prohibited in Brazil by the item I of article 5 of the Constitution (1988). Although prohibited, it is the subject that most divides our population and that constantly returns with force to the media, especially when crimes of great national repercussion happen. Many see it only from perspective of retributive justice and beliefs that it would be an effective solution to reduce criminality. Thus, this study aims to analyze how the big themes about death penalty for the editorials, journalists, guests and readers of the newspaper Folha de São Paulo are structured over four years, 1987, 1993, 2007 and 2015, chosen due to certain events that occurred that rekindled the debate. The research consisted of a document analysis and it was used 94 opinion texts of these social actors that had the expression "death penalty" in the title. Two analysis techniques were applied to achieve different goals: a lexical analysis and a content analysis. The data was first analyzed by the lexical analysis software IRAMUTEQ, which performed a Descending Hierarchical Classification and a Correspondence Analysis. Through them, we wanted to verify what are the subjects that the texts about death penalty are related to and to analyze how the big opinative themes about death penalty were organized and structured over the four years. The program generated five groups of words, indicating that the actors treated the death penalty in Folha under five themes: "Fair/Unfair" (29.7% of the corpus), "International situations" (24.6% of the corpus), "Dissuasive capacity" (20.5% of the corpus), "Rational principles" (12.1% of the corpus) and "Legal principles" (13.1% of the corpus). In a second step, the content analysis was made. Among other points, it sought to analyze how each actor positions themselves and opines about the death penalty over the years and to analyze how the notions of justice and Belief in a Just World are applied to different contexts involving the punishment. The analysis revealed four major categories, "Ineffective", "Cruel", "Nature of crime" and "Legal”, with ten subcategories, and three favorable categories to the punishment: "Retributive justice", "Effective/ Intimidating" and "Popular decision". This analysis showed that crimes considered heinous and of great media coverage tended not to perceive inequality or social injustice by the people and that the belief in a just world is not threatened, turning retributive arguments more frequent. Crimes such as the execution of terrorists and of drug dealers in other countries have further increased this trend. It was also concluded that Folha does not carry out a criminological analysis on the subject, discussing the social question in the country, which is done, in general, by its readers. It should be emphasized that the criminal and penal issue in Brazil is complex and should be done at the societal level, not individual level. Before clamoring for more severe punishments, there are lots of issues that need to be considered and changed, such as public safety, unemployment and the prison system itself.